Pratica monetaria e secolarizzazione moderna - Zhok, Andrea (La moneta di Dio, 2022)
Western modernity is characterized by a process of secularization, combined with the emergence of world views which, in different forms, hinge on a new economic settlement, based on a specific empowerment of monetary exchanges. Both “capitalismµ and “communismµ emerge as visions that, in some way, compete with the traditional sphere of religious bestowal of sense. In these pages we try to evaluate in what form this competition takes place and to what extent it is justified to expect from those ideologies an adequate subrogation of religious functions.